Electrochemical strategy for grown ZnO nanoparticles deposited onto HY zeolite with enhanced photodecolorization of methylene blue: Effect of the formation of Si O Zn bonds - Sapawe, N.; Jalil, A.A.; Triwahyono, S.; Sah, R.N.R.A.; Jusoh, N.W.C.; Hairom, Nur Hanis Hayati; Efendi, J. (Elsevier, 2013)
Nanoparticles of electrogenerated zinc-supported HY zeolite (EGZnO/HY) catalyst were prepared by a simple electrochemical method. The interaction between zinc species and HY support during the electrolysis was found to affect the EGZnO/HY structure. In addition to the formation of EGZnO nanoparticles (<30 nm in size) that distributed on the surface of HY support, an isomorphous substitution of Al with Zn also occurred in the aluminosilicate framework to result in a Si O Zn bonds. The photoactivity of EGZnO/HY was tested on the decolorization of methylene blue (MB). An amount of 0.375 g L−1 of 1 wt% EGZnO/HY was found to be the optimum dosage for 10 mg L−1 MB, which resulted in 80% of maximum decolorization after 6 h of contact time at pH 3 under fluorescent light (420 nm). Increasing the EGZnO loading led to additional formation of Si O Zn bonds and lessened the number of EGZnO nanoparticles, which then reduced the photodecolorization percentage of MB.The photocatalytic reaction was follows the first-order Langmuir–Hinshelwood model, and gives partially mineralization. The photocatalyst was still stable after five cycling runs with no Zn leaching.